Urban Muslims and Educational Choices for Children - Felix Tawaang; Launa Launa (LP. Ma'arif Janggan Magetan, 2023)
The modernization of city life has triggered anxiety among urban muslims regarding the future of their children’s education. This condition was triggered by a shift in the orientation of general education which provides a smaller portion of children’s moral-religious education material. Urban muslims (especially the upper middle class) ultimately see Islamic boarding schools, madrasas, and modern Islamic schools (integrative curriculum-based or Integrated Islamic Schools/IIS)—which provide a larger portion of moral-religious material—as alternative schools for their children. their child. This qualitative study using Max Weber’s social action theory approach and literature review analysis method tries to analyze the factors behind upper-middle class urban parents choosing Integrated Islamic Schools (IIS) as a place to study for their children. This study concluded that internal factors (the importance of inheriting religious values), external factors (the influence of an increasingly religious social and family environment), and performance factors (parents’ personal motives) were the three main factors that became dominant motives.